SHIP BALLAST WATER EXCHANGE METHODS ON BOARD SHIPS - da Rocha Neto, José Lucena; Muniz Santos, Marcelo (Journal of Interdisciplinary Debates, 2021)
The IMO established rules for ballast water exchange procedures to be carried out in oceanic regions. There are three known methods: - Sequential method; - Overflow or continuous flow method; - Brazilian dilution method. All three are not 100% efficient. It is known that they present structural problems to the ship, and even so they do not guarantee total effectiveness in the elimination of exotic species. In addition to these methods, other types of methods are already being tested at American Universities. The present work presents in-depth studies on ballast water exchange procedures.